Bài 2: Mình nghĩ câu a là a+2b-3c=-20
a) Ta có: a/2 = b/3 = c/4 = 2b/6 = 3c/12 = a + 2b - 3c/ 2 + 6 - 12 = -20/-4 = 5
a/2 = 5 => a = 2 . 5 = 10
b/3 = 5 => b = 5 . 3 = 15
c/4 = 5 => c = 5 . 4 = 20
Vậy a = 10; b = 15; c = 20
b) Ta có: a/2 = b/3 => a/10 = b/15
b/5 = c/4 => b/15 = c/12
=> a/10 = b/15 = c/12 = a - b + c / 10 - 15 + 12 = -49/7 = -7
a/10 = -7 => a = -7 . 10 = -70
b/15 = -7 => b = -7 . 15 = -105
c/12 = -7 => c = -7 . 12 = -84
Vậy a = -70; b = -105; c = -84.
Bài 1:
Ta có: a:b:c:d = 2:3:4:5
=> a/2 = b/3 = c/4 = d/5 = a+b+c+d/2+3+4+5 = -42/14 = -3
a/2 = -3 => a = -3 . 2 = -6
b/3 = -3 => b = -3 . 3 = -9
c/4 = -3 => c = -3 . 4 = -12
d/5 = -3 => d = -3 . 5 = -15
Vậy a = -6; b = -9; c = -12; d = -15.
Ta có: a:b:c:d = 2:3:4:5
=> a/2 = b/3 = c/4 = d/5 = a+b+c+d/2+3+4+5 = -42/14 = -3
a/2 = -3 => a = -3 . 2 = -6
b/3 = -3 => b = -3 . 3 = -9
c/4 = -3 => c = -3 . 4 = -12
d/5 = -3 => d = -3 . 5 = -15
Vậy a = -6; b = -9; c = -12; d = -15.
Cảm ơn bạn Vĩnh Thụy nhé.Mình đã k rồi đó